Operations research and enterprise systems : 5th International Conference, ICORES 2016, Rome, Italy, February 23-25, 2016, Revised selected papers /: 5th International Conference, ICORES 2016, Rome, Italy, February 23-25, 2016, Revised selected papers. (2017) - Unknown
No abstract available